Diversity of water bugs (Hemiptera) over different landscapes in some provinces of Northern Vietnam - Phan Thi Giang; Quang Cuong, Nguyen; Thanh Manh, Nguyen; Thi Hanh, Nguyen; Thi Thanh, Nguyen; Lam, Truong Xuan (Academia Journal of Biology, 2023)
The studies involving water bugs (Hemiptera) biodiversity and ecology are very few and have mainly focused on taxonomy. We conducted research and evaluation of diversity indexes of water bugs (Hemiptera) in different landscapes including forest habitats, agricultural lands, ponds, streams from 16 sampling sites in Bac Kan, Lao Cai, Ninh Binh and Ha Tinh provinces. As a result, a total of 43 species of 23 genera of 10 families were recorded. The Shannon index (H′), the Simpson index (1-D), the Berger-Parker index of dominance, the Margalef index and the Fisher alpha index did not differ much between study sites. The evenness of water bugs (Hemiptera) was divided into 4 different main groups for 16 sampling sites. The Shannon index (H′), Simpson (1-D) index, species richness and individual rarefaction in forest habitats are higher than in agricultural land. However, the species richness was no different in ponds and streams.